Death, Power, and Apotheosis in Ancient Egypt : The Old and Middle Kingdoms - Troche, Julia, 1986- (Book collections on Project MUSE., 2021)
"Explores the perceived agency of esteemed dead in ancient Egyptian social, political, and religious life, during the Old through Middle Kingdoms (c. 2700-1650 BCE). It considers how power was constructed, maintained, and challenged in ancient Egypt, through the particular lens of mortuary culture and apotheosis-i.e. deification"--